2008
DOI: 10.1002/cyto.a.20598
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Phospho‐Flow cytometry reveals novel insights into TCR proximal signaling events. A comparison with Western blot

Abstract: Phospho-site specific antibodies become increasingly available, enabling the study of signaling events by Western blotting (WB) or intracellular flow cytometry (PhosphoFlow). Here we compared data generated by WB or Phospho-Flow regarding the kinetics and degree of phosphorylation of membrane proximal TCR signaling molecules. Phosphorylation events in Jurkat T cells were triggered by anti-CD3 stimulation (OKT3) or by oxidative stress (H 2 O 2 ) and were analyzed by Phospho-Flow or WB. Both techniques showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 13 publications
(15 reference statements)
2
16
0
Order By: Relevance
“…Phospho-flow has been shown to be an excellent tool to detect intracellular signaling in complex populations of cells [15] including Zap70 phosphorylation in CD4 + T cells [16]. We show that Zap70 phosphorylation occurs within few minutes of Tresp stimulation and is detected for only 10 minutes, similar to the short period of Zap70 phosphorylation previously reported [11]. Treg were reported to require several hours for exerting their effect on Tresp [9], therefore we employed a "2-stages approach" for activating Treg and then measuring Zap70 phosphorylation in Tresp using anti-CD3 and anti-CD28 antibodies for both stages.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Phospho-flow has been shown to be an excellent tool to detect intracellular signaling in complex populations of cells [15] including Zap70 phosphorylation in CD4 + T cells [16]. We show that Zap70 phosphorylation occurs within few minutes of Tresp stimulation and is detected for only 10 minutes, similar to the short period of Zap70 phosphorylation previously reported [11]. Treg were reported to require several hours for exerting their effect on Tresp [9], therefore we employed a "2-stages approach" for activating Treg and then measuring Zap70 phosphorylation in Tresp using anti-CD3 and anti-CD28 antibodies for both stages.…”
Section: Discussionsupporting
confidence: 85%
“…These events induce transcription of diverse gene products, culminating in cytokine secretion by T cells as well as proliferation and enhancement of other T cell functions [10]. Zap70 phosphorylation occurs within minutes after activation of T cells [11]. Accordingly, we hypothesized that activated Treg can suppress Zap70 phosphorylation in activated Tresp.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that flow cytometry can generate qualitative results concerning dose responses and kinetics of signaling molecules similar and complementary to the data obtained with blotting techniques (19,(26)(27)(28). Flow cytometry does not require a purification of the basophils.…”
Section: Discussionmentioning
confidence: 84%
“…Cells were stained with antibodies against phospho-LCK (#558552; BD Biosciences, Franklin Lakes, NJ), phospho-SRC (#560096; BD Biosciences), cleaved Poly(ADP-ribose) polymerase (PARP) (#560640; BD Biosciences) and CD3 (#562426; BD Biosciences). A similar assay was previously described for T-cell phosphoflow analysis using CD3/CD28 and H 2 O 2 stimuli (38,39). Data were acquired on a FACSVerse flow cytometer and analyzed with FCS Express (version 4; BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%